Teaching Speaking Class By Native Speaker For The First Semester Students Of English Department Of Muhammadiyah University Of Surakarta In 2011/2012 Academic Year - Nuryanti, Nuryanti; , Anam Sutopo, S.Pd. M.Hum; , Nur Hidayat, S.Pd (2013)
This research paper is intended to 1) analyze the procedure of native speaker that teaches speaking for the first semester of English Department in Muhammadiyah University of Surakarta, 2) describe the problems for the teacher and students in speaking class for the first semester of English Department in Muhammadiyah University of Surakarta. This research is descriptive qualitative which does not include any calculation or statistic procedure. Method of collecting data involves observation and interview. The data are taken from the subject of this research in the form of observation, interview and document. Subject of the study is limited on the first semester of English department students in 2011/2012 academic year. She took class C that consists of 18 students. The result of this study shows that 1) the procedure of teaching speaking by the teacher are effective. Because, by using that procedures are being more confident and relaxing to practice speaking in the speaking class activity. The native speaker procedures are opening, core learning and closing. The opening as the gate to deep comprehension, core learning is the essence of learning and closing is the conclusion of the learning. The teaching learning speaking activity are; games, drama, dialogues, and individual assessment, 2) there are some problems that appear from the implementation of the teaching procedure faced by the students and the teacher. From the students there are, lack of grammar, pronunciation, vocabulary, and self management (shy, nervous, and unconfident to say). From the teacher are the social background between the teacher and the students and the different speaking level (heterogeneity) of the students. The class condition didn't improve the speaking class because the class is too large and wide and not balance with the number of the students consisting of 18 until 25 students, resulting no clear voice acceptance, no supporting at atmosphere because no concentration, difficult to be handed by the teacher.